Age-associated B Cells Appear in Patients with Granulomatous Lung Diseases - Phalke, Swati; Aviszus, Katja; Rubtsova, Kira; Rubtsov, Anatoly; Barkes, Briana; Powers, Linda; Warner, Brenda; Crooks, James L.; Kappler, John W.; Fernández-Pérez, Evans R.; Maier, Lisa A.; Hamzeh, Nabeel; et al. (American journal of respiratory and critical care medicine, 2020)
A subpopulation of B cells (age-associated B cells [ABCs]) is increased in mice and humans with infections or autoimmune diseases. Because depletion of these cells might be valuable in patients with certain lung diseases, the goal was to find out if ABC-like cells were at elevated levels in such patients. To measure ABC-like cell percentages in patients with lung granulomatous diseases. Peripheral blood and BAL cells from patients with sarcoidosis, beryllium sensitivity, or hypersensitivity pneumonitis and healthy subjects were analyzed for the percentage of B cells that were ABC-like, defined by expression of CD11c, low levels of CD21, FcRL 1-5 (Fc receptor-like protein 1-5) expression, and, in some cases, T-bet. ABC-like cells in blood were at low percentages in healthy subjects and higher percentages in patients with sarcoidosis as well as at high percentages among BAL cells of patients with sarcoidosis, beryllium disease, and hypersensitivity pneumonitis. Treatment of patients with sarcoidosis led to reduced percentages of ABC-like cells in blood. Increased levels of ABC-like cells in patients with sarcoidosis may be useful in diagnosis. The increase in percentage of ABC-like cells in patients with lung granulomatous diseases and decrease in treated patients suggests that depletion of these cells may be valuable.